A library at the touch of a finger-tip: an analysis of mobile library services at the University of the West Indies, Mona campus. Issue 1 (9th December 2020) - Duncan, Adrian St. Patrick
Abstract : Purpose: The purpose of this paper is to assess the state of mobile library services available for students' information needs at the University of the West Indies, Mona Campus. In addition, this study will determine the extent to which mobile services has helped the Mona libraries to have greater reach to students. Design/methodology/approach: Surveys and content analysis were used to collect data. A comparative content analysis was used to highlight the strides made in mobile library services in universities across the world vis-à-vis the current reality in the Caribbean, specifically Jamaica. Findings: The findings identified that there is a proliferation of mobile and internet users among university and college students and they are heavily using their devices for the furtherance of their educational attainment. Additionally, the findings indicated that libraries in the academic realm can benefit greatly from allowing their content to be accessible through these mobile devices, as it would also help with greater usage. Furthermore, this service is guaranteed greater support the distance programmes offered by these universities. Research limitations/implications: This study will focus on assessing the state of mobile library services offered at the University of the West Indies, Mona Jamaica. This study will also determine the extent to which mobile services can help libraries to have greater reach to students and provide best practices for academic libraries implementing mobile service offerings to clients. This study will not attest to the financial feasibility of academic institutions to start such a programme. Practical implications: The research excavated that the University of the West Indies, Mona Campus, along with other academic libraries in the Caribbean are all not fully offering mobile library services to all their users. In addition, with the rise of technology and the proliferation of cell phones and other mobile devices, students (distance and onsite) expect a service that allows them greater access to the offerings of the university and their libraries. Originality/value: This is the premier investigation of its kind into how the University of the West Indies Mona Campus has responded to the mobile library environment. The value of this research is in helping academic and university libraries in the Jamaica to identify the importance of leveraging the benefits of the dynamic technological era, allowing greater and wider reach through mobile library services proliferation and access to services. In addition, this study showed that academic libraries need to enhance services in a bid to provide greater support the teaching component of the university or college they serve.